2009
DOI: 10.1088/0953-8984/21/39/395801
|View full text |Cite
|
Sign up to set email alerts
|

Atomic structure of As2S3–Ag chalcogenide glasses

Abstract: Abstract(As 0.4 S 0.6 ) 100-x Ag x glasses (x = 0, 4, 8, 12 at.%) have been studied with high-energy x-ray diffraction, neutron diffraction and extended x-ray absorption spectroscopy at As and Ag Kedges. The experimental data were modelled simultaneously with the reverse Monte-Carlo simulation method. Analysis of the partial pair correlation functions and coordination numbers extracted from the model atomic configurations revealed that silver preferentially bonds to sulphur in the As 2 S 3 -Ag ternary glasses,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Silver induces the dissociation of S-S chains in behalf of the formation of AgS 3/2 pyramids. Sulfur atoms in remaining As-S-As links are eliminated, resulting in the formation of As-As bonds [34] (Figs. 9(a)-(b)).…”
Section: Characterization Of the Photoinduced Structural Changes By Rmentioning
confidence: 99%
“…Silver induces the dissociation of S-S chains in behalf of the formation of AgS 3/2 pyramids. Sulfur atoms in remaining As-S-As links are eliminated, resulting in the formation of As-As bonds [34] (Figs. 9(a)-(b)).…”
Section: Characterization Of the Photoinduced Structural Changes By Rmentioning
confidence: 99%
“…Modern technological applications include mouldable intra-red optics and fibers, lenses, memory devices, and phase change materials. High energy X-ray diffraction studies have been carried out on selenides [85][86][87][88][89][90][91], for example, see Figure 4, sulfides [92][93][94][95][96][97][98], arsenides [96][97][98], tellurites [99][100][101][102][103][104], and chalcohalides [105][106][107]. Bychkov et al found a complex variation in network formation and destruction versus composition in binary chalcogenides [85].…”
Section: Experiments On Glasses and Liquidsmentioning
confidence: 99%
“…Bychkov et al found a complex variation in network formation and destruction versus composition in binary chalcogenides [85]. Chemical ordering effects [98] and conduction pathways in fast-ion conducting chalcogenide glasses have also been an area of significant interest relating structure to changes in ion transport [87,88,94,95,[105][106][107].…”
Section: Experiments On Glasses and Liquidsmentioning
confidence: 99%
“…Ag binds preferentially to excess S atoms and avoids As. It is to be mentioned that in the As 2 S 3 -Ag glasses Ag-As bonding was observed [34]. The comparison of As K-edge EXAFS spectra of AsS 2 -Ag glasses (Fig.…”
Section: Pairsmentioning
confidence: 92%